2014
DOI: 10.1166/mex.2014.1190
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of hafnium oxide nanoparticles for bio-safety

Abstract: In recent years, the perspective of applying hafnium oxide (HfO 2 ) has geared up in various field of medical science such as neutron detection, bioimplants, biosensors, radiotherapy etc., The present study is to synthesis HfO 2 nanoparticles, and check its cell viability for in vivo applications. Hafnium oxide nanoparticles of different sizes (8.79, 7.16, 6.78 nm) were synthesized by varying the intervals of stirring time (6 h, 8 h, 12 h) by precipitation method. XRD pattern and Raman spectroscopy revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…4,5 It oen plays an important role in the continuous down-scaling of integrated circuits since new insulating materials with a high dielectric constant are being researched to replace SiO 2 as a gate dielectric. 6,7 In terms of structural characteristics, hafnium oxide exists in three polymorphic structures, namely monoclinic (m-HfO 2 ) at low temperature, tetragonal (t-HfO 2 ) above 2050 K, and cubic (c-HfO 2 ) at around 2803 K. [8][9][10] Each structure has different applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 It oen plays an important role in the continuous down-scaling of integrated circuits since new insulating materials with a high dielectric constant are being researched to replace SiO 2 as a gate dielectric. 6,7 In terms of structural characteristics, hafnium oxide exists in three polymorphic structures, namely monoclinic (m-HfO 2 ) at low temperature, tetragonal (t-HfO 2 ) above 2050 K, and cubic (c-HfO 2 ) at around 2803 K. [8][9][10] Each structure has different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, researchers have developed some synthesis approaches such as gel-sol method, 13 microemulsion processes 14 and precipitation. 10,15 However, these methods have some drawbacks, such as complicated operation, low yield and agglomerated products. In addition, all these ways only can obtain the m-HfO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…A precipitation method was used to synthesize HfO 2 NPs. A 0.4 M (50 mL) aqueous solution of NaOH was added dropwise into a 0.1 M (50 mL) aqueous solution of HfCl 4 under continuous stirring for 6 hours to obtain white hafnium hydroxide precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [16][17][18][19][20][21][22] has demonstrated the promising results for the application of nanoparticles of some metal dioxides and of solid solutions, which are composed so that they will have utility in biomedical applications. The additives, which provide certain functional properties to nanostructured materials, in particular, luminescent properties, are often used in the aforementioned nanoparticles as an admixture component.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that though there are several studies [16][17][18][19][20][21][22] dedicated to the biological effects of the nanoparticles, which are based on metal dioxides such as TiO 2 , HfO 2 , CeO 2 , and solid solutions containing them, there is considerably less information about the biological effect of zirconium dioxide-based nanoparticles [30][31][32]. However, since zirconium dioxide based nanopowders, solid solutions, nanocomposites and other ZrO 2 -containing nanomaterials, have become widely spread in scientific research and technological applications [33][34][35][36][37], studying their biological effect is important.…”
Section: Introductionmentioning
confidence: 99%